Linguistic hybridity and learner identity: translingual practice among plurilinguals in the educational setting - Lankiewicz, Hadrian Aleksander (Neofilolog, 2021)
Capitalizing on the ecological approach to language learning (van Lier, 2004; Kramsch, 2008) and the conceptualization of language as a local practice (Pennycook, 2010) as well as languaging (Jørgensen, 2008), accounting for the continuity of linguistic phenomena rather than a discriminatory perception of linguistic properties, we intend to delve into the problem of linguistic hybridity as a sign of L2 learner identity. A direct inspiration for the study, as exemplified in the title, is the concept of metrolingualism (Otsuji, Pennycook, 2010), which offers a potential to be very informative for the study of identity issues inscribed in language. Metrolingualism connotes linguistic hybridity, which refers to something unnatural, untypical, not conforming to the norm. Positing the continuity of language use and symbolic competence (Kramsch, Whiteside, 2008), we assume after van Lier (2004) that language is not a fixed code but socially constructed entity which mingles with personal experiences shaped by social context and activates power-related issues in language use. The aim of the paper is to delve into discursive practices of students learning/using more than one L2 in the educational setting. An examination of their narratives and their languaging about language (Swain, 2006) discloses how they position themselves as L2 language users.